PENGEMBANGAN PARIWISATA BERBASIS KEARIFAN LOKAL DI PANTAI LON MALANG KABUPATEN SAMPANG - Rahman, Slamet Adi; Setiyarini, Triana (JURSIMA, 2022)
Lon Malang Beach in Sampang, Indonesia, is a location with significant tourism potential. With its natural beauty, local culture, and unique natural resources, the beach is an attractive destination for tourists. The beach has great tourism potential, but the lack of awareness of culture, local wisdom, and Madura/Sampang specialty products is hindering its development as an impressive and attractive tourist destination.This study used a qualitative approach with the SWOT analysis method. Data collection techniques included primary and secondary data. Primary data was obtained from the field, such as information from direct observations at the research location by observation and interviews. Secondary data is data that is obtained from a third party, either in the form of notes, such as books, theses, journals, and articles that are documentary in nature.The results of the study showed that internally, the development of local wisdom-based tourism at Lon Malang Beach has a relatively strong position internally compared to external factors. In addition, there are alternative SO, ST, WO, and WT strategies that are produced by SWOT analysis that can be applied to the development of local wisdom-based tourism at Lon Malang Beach. The results of this study are expected to provide a deep insight into the development of local wisdom-based tourism at Lon Malang Beach, Sampang Regency.